2020
DOI: 10.5194/wes-5-983-2020
|View full text |Cite
|
Sign up to set email alerts
|

New strategies for optimized structural monitoring of wind farms: experimental campaign

Abstract: Abstract. The main goal of the recently started WindFarmSHM research project is the development, validation and optimization of monitoring strategies to be applied at the level of the wind farm. These strategies should be able to evaluate the structural condition of a set of wind turbines and their consumed fatigue life using the response to operation loads. In this context, a quite extensive experimental campaign is being performed at the Tocha wind farm, an onshore wind farm located in Portugal, which includ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 9 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…A detailed description of the monitoring system is presented in Oliveira et al 11 In this application, the instrumentation is limited to the tower; still, it will be demonstrated that some modes dominated by the rotor can be followed. However, for a full characterization of the dynamic behavior of the wind turbine measurements at the blades are recommended, which can be done using the sensors described in Pacheco et al 19 …”
Section: Resultsmentioning
confidence: 99%
“…A detailed description of the monitoring system is presented in Oliveira et al 11 In this application, the instrumentation is limited to the tower; still, it will be demonstrated that some modes dominated by the rotor can be followed. However, for a full characterization of the dynamic behavior of the wind turbine measurements at the blades are recommended, which can be done using the sensors described in Pacheco et al 19 …”
Section: Resultsmentioning
confidence: 99%
“…This windfarm included 5 VESTAS V100 wind turbines, labelled from WT1 to WT5, with a rated power of 1.8 MW. The experimental campaign, described in detail in [20] for which 10-min averaged SCADA data was also available, includes accelerometers and strain gauges installed in both the tower and the blades of WT1 and WT5 (WT1 with the 3 blades instrumented and WT5 with two blades instrumented), namely a set of fibre optic strain gauges at each blade's root and the MEMS accelerometers described above placed at roughly 10m from the root, as represented in Figure 5. The methodology that will be presented in the following section will rely only on the latter.…”
Section: Experimental Campaign Overviewmentioning
confidence: 99%
“…However, only the dynamic monitoring system of the tower accelerations and strains installed in wind turbine 1 are briefly described in this paper. A detailed description of the Tocha Wind Farm experimental campaign, as well as some preliminary results, can be found in [65].…”
Section: Tower Monitoring Systemmentioning
confidence: 99%